2023
DOI: 10.1021/acsami.2c17691
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling the Tumor Microenvironment with Core–Shell Nanosensitizer Featuring Dual-Modal Imaging and Multimodal Therapy for Breast Cancer

Abstract: To improve the efficiency of radiation therapy (RT) for breast cancer, a designable multifunctional core–shell nanocomposite of FeP@Pt is constructed using Fe(III)-polydopamine (denoted as FeP) as the core and platinum particles (Pt) as the shell. The hybrid structure is further covered with hyaluronic acid (HA) to give the final nanoplatform of FeP@Pt@HA (denoted as FPH). FPH exhibits good biological stability, prolongs blood circulation time, and is simultaneously endowed with tumor-targeting ability. With C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…The fluorescent probe [Ru(dpp) 3 ]Cl 2 (RDPP, dpp = 4,7‐diphenyl‐1,10‐phenanthroline), when co‐incubated with oxygen‐depleted cells, shows red fluorescence and is quenched as the intracellular O 2 content increases. [ 67 ] As shown in Figure 4b,c, it could be observed that the red fluorescence of RDPP in the LPS‐induced RAW 264.7 cells was very bright, indicating very low O 2 content. The hypoxia state could hardly be alleviated under exclusively MW irradiation (3 W, 450 MHz, 5 min).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescent probe [Ru(dpp) 3 ]Cl 2 (RDPP, dpp = 4,7‐diphenyl‐1,10‐phenanthroline), when co‐incubated with oxygen‐depleted cells, shows red fluorescence and is quenched as the intracellular O 2 content increases. [ 67 ] As shown in Figure 4b,c, it could be observed that the red fluorescence of RDPP in the LPS‐induced RAW 264.7 cells was very bright, indicating very low O 2 content. The hypoxia state could hardly be alleviated under exclusively MW irradiation (3 W, 450 MHz, 5 min).…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescent probe [Ru(dpp) 3 ]Cl 2 (RDPP, dpp = 4,7-diphenyl-1,10-phenanthroline), when co-incubated with oxygen-depleted cells, shows red fluorescence and is quenched as the intracellular O 2 content increases. [67] As shown in Figure 4b,c Many studies have shown that excessive ROS in RA leads to oxidative stress and aggravates the occurrence and development of inflammation. [68] To confirm the ROS elimination capacity of UMnEH, we used 2′,7′-dichlorodihydrofluorescein diacetate (DCFH-DA) as a probe to monitor the ROS level in the LPSinduced RAW 264.7 cells.…”
Section: The Capacity Of Umneh Producing Intracellular Oxygen and Sca...mentioning
confidence: 95%
“…Hence, developing a Cu/Fe bimetal-based Fenton reagent is highly desired to induce efficient Ferroptosis. On the other hand, eliminating intracellular reactive oxygen species (ROS)-scavenging substances like GSH is necessary to avoid the brake on Ferroptosis. , However, the integration of these two functions into one nanoplatform is still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Changing the layer thickness of the core-shell structures or the contents of other materials in the layers can also produce many excellent properties, giving them a wide range of applications [ 30 , 32 ]. For example, in the field of biomedicine, core-shell nanoparticles are mainly used for controlled drug transport [ 33 ], the imaging of organisms, cellular labeling [ 34 ], biosensors [ 35 ], and regenerative medicine [ 36 ]. Through scientific design, it is possible to obtain core-shell and variously shaped structures, including strawberry-type [ 37 ], snowman-type, and island-type [ 38 ].…”
Section: Introductionmentioning
confidence: 99%